The investigation, creation and formulation of novel thermochromic coatings - Mackilligin, Harry (2017)
Rolls-Royce is a well reputed and multinational company that develops and manufactures propulsion systems including gas turbines for many applications, with aerospace being the most well-known. In the process of developing new turbine engines to power ever larger, more efficient and environmentally friendly aircraft, the conditions within their engines are pushing the boundaries of what was previously thought possible. One of the major factors that needs to be considered and controlled in the engine development is the temperature at which the engine components are exposed to. Currently, temperatures produced within their engines are in excess of 1600 °C, which is far beyond the melting point of the metal alloys that make up the engine itself. Due to this, many creative cooling technologies have been modelled and implemented to reduce the temperatures experienced by engine components. These cooling technologies must be validated in situ with precise temperature analysis tools that can give accurate temperature readings on moving parts, deep within the engine. Of the tools available, thermal paints have proven to be highly effective and versatile. Thermal paints are irreversible thermochromic coatings that are applied to component surfaces, and on deconstruction of an engine, reveal the maximum temperatures reached and give a visual display of temperature gradients across a surface. These paints have been used within Rolls-Royce for over 50 years and are now a focal point for development due to recent REACH legislation preventing the use of many outdated pigments that are used within the paint formulations. This project was created to build an understanding of the chemistry behind the thermochromic effect and to develop new, safer thermochromic paints to secure the techniques future within the development of state of the art turbine engines. Two of Rolls-Royce’s thermal paints, TP11 and TP8, have been fully investigated and the previously unknown chemistry behind the thermochromic effect exhibited by these paints has been identified (Chapter 3). From the information gained from this initial investigation, new thermochromic paints based on REACH compliant compounds have been produced and characterised. The results obtained from this work have shown great promise and have had an influential impact within the aerospace industry.